Patterns and predictors of site‐specific recurrence in cervical cancer after radical hysterectomy. Issue 12 (29th September 2022) - Kato, Tatsuya; Shimada, Chisa; Kato, Fumi; Okada‐Kanno, Hiromi; Takeda, Mahito; Endo, Daisuke; Ihira, Kei; Mitamura, Takashi; Konno, Yosuke; Sakuragi, Noriaki; Watari, Hidemichi
Abstract: Aim: This study examines patterns and predictors of site‐specific recurrence to explore the causes of local recurrence of cervical cancer. Methods: Radical hysterectomy was performed in 121 patients (stage IB–IIB). Nerve‐sparing was performed whenever possible. The first recurrence in local, regional, and distant areas was examined. We investigated the possibility of nerve involvement in local recurrence, focusing on paravaginal tissues containing the pelvic plexus. We provide Supporting Information on local recurrence in the paravaginal area. Results: Local recurrence was an independent event from regional or distant recurrence. Local recurrence was seen only in high‐risk patients, while regional and distant recurrences were not or less related to the risk category. The independent risk factors by logistic regression for local, regional, and distant recurrence were parametrial invasion, vaginal invasion, and lymph node metastasis, respectively. Local recurrence showed a comparable or more significant negative impact on survival than distant recurrence. Among seven patients with local recurrences, five had a recurrence in the paravagina. The rate of paravaginal recurrence was one in 76 early‐stage and four in 45 locally advanced diseases. Four sites of paravaginal recurrence occurred on the nerve‐sparing side and two on the non‐nerve‐sparing side. Supporting Information demonstrated histological evidence of perineural spread into the pelvic plexus and perineural invasion of the primary tumor. Conclusions: A high percentage of local recurrences are in paravaginal tissue containing the pelvic plexus. The causal association of nerve‐sparing surgery and perineural invasion with local recurrence needs to be investigated in large prospective studies.